Frequency of Hyponatremia in Adult Patients with Community Acquired Pneumonia Presenting at Pulmonology Ward of Mardan Medical Complex - Abdullah, Muhammad; Ali, Sajjad; Ahmad, Imtiaz; Bahadur, Zeeshan (Indus Journal of Bioscience Research, 2025)
Background: Hyponatremia is often seen in hospital patients, especially those with respiratory infections. The development of electrolyte imbalances in community-acquired pneumonia happens mainly through when antidiuretic hormone is secreted inappropriately, fluid is lost and pro-inflammatory molecules are released. Objective: To determine the frequency of hyponatremia in adult patients with community acquired pneumonia presenting at pulmonology ward of Mardan medical complex. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from July 2024 to January 2025 in the Pulmonology Department of Mardan Medical Complex, Peshawar. Methodology: 110 patients aged 25 to 70 years who had verified community-acquired pneumonia took part in the study. The patient was diagnosed based on how they presented and radiological images indicating lobar pattern and consolidation. Those with a history of pregnancy, lactation or lasting issues with their kidney or liver were excluded. Hyponatremia is present when serum sodium is measured at less than 130 mmol/L. Results: The mean age of patients was 47.19 ± 11.82 years, with 68 males (61.8%) and 42 females (38.2%). Hyponatremia occurred in 32 patients (29.10%). Advanced age (>50 years) was the strongest predictor with 65.2% hyponatremia rate versus 3.1% in younger patients (p<0.001). Elevated BMI (>25 kg/m²) showed 49.0% versus 13.1% in normal weight patients (p<0.001). Conclusion: Hyponatremia affects nearly one-third of adults with community-acquired pneumonia, with advanced age, elevated BMI, diabetes mellitus, and hypertension.